Peranan Guru Besar Dalam Pengurusan Kokurikulum Daripada Perspektif Guru Penasihat Kokurikulum Sekolah Rendah di Zon Cheras, Daerah Hulu Langat, Selangor - Zakaria, Azmi; Mansor, Ahmad Zamri (Selangor Humaniora Review, 2019)
This study aims to examine co-curricular advisory teachers’ perspective on the role of principals in managing co-curricular activities in national schools in the zone of Cheras, Hulu Langat. The roles of the principals were examined based on the aspects of them as leaders, planners, coordinators, and supervisors of the co-curricular. This quantitative study used a survey technic in its attempt to see the difference in the role of the principals in the management of co-curricular against demographic factors such as gender, school grades and working experience as well as the relationship with the school’s achievement in cocurricular activities. The samples of the study were 338 teachers who are currently serving as co-curricular advisory teachers. The samples were randomly selected. Data was collected using a questionnaire that was attested and accredited by experts. The data obtained were analyzed using a descriptive method to explain the mean score and the standard deviation in describing each dimension studied using Statistical Packages for Social Sciences (SPSS) version 22. The findings showed that the co-curricular advisory teachers’ perspective of the principals in the schools studied were that, they are effective leaders, successful in implementing their management roles as leaders, planners, coordinators and supervisors in ensuring the successful implementation of co-curricular activities in schools.